国际语言服务学科的基础理论探析. - 崔启亮; 张小奇 (Journal of Beijing International Studies University, 2026)
International Language Service (ILS) was approved by the Ministry of Education of the People’s Republic of China as a secondary discipline under Foreign Languages and Literature in 2021. To promote the development of the disciplinary system of ILS, it is necessary to study its theoretical foundation. From an interdisciplinary perspective, this paper focuses on the core issues of the theoretical foundation of the ILS discipline and constructs a theoretical framework of the ILS discipline that has both academic depth and practical explanatory power. The study fi nds that Translation Studies, Foreign Linguistics and Applied Linguistics, Computer Application Technology, Cross-Cultural Studies, Industrial Economics, and Service Trade Studies jointly constitute the theoretical foundation of the ILS discipline. Among them, Translation Studies and Foreign Linguistics and Applied Linguistics are the core theories, Computer Application Technology and Cross-Cultural Studies are the general theories, and Industrial Economics and Service Trade Studies are the interdisciplinary theories.